Circularly Polarized Cross-Dipole Array Antenna for GNSS and L-Band Satellite Applications - Aliakbar Dastranj; Hamed Shirzad (IEEE Access)
This study introduces a dual-sense circularly polarized (CP) crossed-dipole array antenna designed for Global Navigation Satellite System (GNSS) frequency bands. The antenna employs an optimized double-branch line coupler (ODBLC) and a single pair of dual-band linearly polarized dipole antennas (LPDAs) to achieve impedance bandwidths of 44.83% (1092.1–1723.3 MHz) for right-hand circular polarization (RHCP) and 46.30% (1070.2–1715.1 MHz) for left-hand circular polarization (LHCP), with axial ratio bandwidths of 47.69% and 44.78%, respectively. With peak gains of 7.08–7.10 dBic and a compact form factor of $160× 160× 44.6$ mm3, the simplified feed architecture enhances manufacturability and reduces fabrication costs. The dual-sense circular polarization mitigates multipath interference in urban, forested, and maritime environments, facilitating applications in precision navigation, autonomous vehicle localization, geodetic surveying, and meteorological data acquisition.